Pengaruh Pelaksanaan Simulasi Siaga Bencana Kebakaran terhadap Pengetahuan dan Sikap Warga SMP Agustinus Kota Semarang - Hany Risna Afida; Anik Setyo Wahyuningsih (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Central Java was recorded as the area with the highest fire rate in the period from January 1 to July 24 2023, with 637 cases recorded. In 2018, a fire hit Agustinus Junior High School, at Semarang City. The aim of the research is to determine the effect of implementing a fire disaster preparedness simulation in increasing the knowledge and attitudes of Agustinus Middle School residents regarding fire disasters. The research design used was a quasi experiment with a quantitative approach. This research used a one group pretest-posttest design. In this research design, the entire population is used as research respondents. The pretest was given before the fire disaster simulation activity began and the posttest was given after all respondents carried out the fire disaster simulation activity. The research instrument used a questionnaire sheet. Data were analyzed with wilcoxon test. The results of the research show that there is an effect of implementing a fire disaster preparedness simulation on the knowledge and attitudes of Agustinius Junior High School residents with a wilcoxon p value of 0.000 and there is an increase in the knowledge of the school community by 24.3% and the attitude of the school community by 34% compared to before the simulation. This research suggests that schools should hold regular disaster preparedness simulations at least once a year and collaborate with related professional institutions to increase the capability and effectiveness of school emergency response teams in handling emergency situations.